Making the portrait of Khalil al-Khuri (1836–1907): writer, orthodox freemason, ottoman bureaucrat - Evgeniy Kopot (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
Khalil al-Khuri, born into an Orthodox family, was, along with Butrus al-Bustani, one of the main figures of the Arab Nahda era. Having become the first Lebanese to publish an Arabic-language newspaper in Beirut, «Hadiqat al-Akhbar», Khury published almost 3,000 issues during its more than half-century history (1858-1911). In 1858, he was the first to publicly present the concept of Syrianism in his newspaper. This institution became an important mechanism for creating an “imagined community” of Syrians and forging a new secular identity. At the same time, Khalil al-Khuri was one of the main enemies of the Orthodox community, interfering in the affairs of the church as an Ottoman official. In 1885 and 1891 he took part in the election of the Antiochian Patriarch and, in the interests of the Ottoman administration, contributed to the defeat of the “Arab” party, objectively hindering the consolidation of Orthodox Arabs around the patriarch. This article reconstructs for the first time his role in the internal life of the Antiochian Patriarchate in the second half of the 19th century. An attempt is made to interpret the dynamics of Khalil al-Khuri’s self-identification from an Orthodox Lebanese in 1857 to an anticlerical freemason in 1885-1891.